2014
DOI: 10.1080/02687038.2013.878452
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and auditory processing ability in people with aphasia

Abstract: Background: Hearing loss can add to the linguistic deficits present in aphasia to make comprehension of speech difficult. Although some studies document a relatively high prevalence of hearing loss in adults with aphasia, many people with aphasia do not have their hearing tested. Self-reported disability measures offer a possible alternative to pure-tone audiometry when this service is not readily available. Aims: This study aims to investigate the prevalence of hearing loss in a group of people with aphasia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…These issues eventually lead to functional impairments and overall reduction in quality of life [63, 64]. Considering that prosodic processing impairments, communication deficits and emotion recognition deficits are also associated with psychosocial problems [53, 65], it raises the importance of identifying prosodic processing issues at early stages of the injury to reduce medical burden and improve outcomes for survivors of TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues eventually lead to functional impairments and overall reduction in quality of life [63, 64]. Considering that prosodic processing impairments, communication deficits and emotion recognition deficits are also associated with psychosocial problems [53, 65], it raises the importance of identifying prosodic processing issues at early stages of the injury to reduce medical burden and improve outcomes for survivors of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the studies included examined prosodic impairment post-TBI despite the initial literature search terms that included a large and comprehensive list of language disorders. It is alarming that none of the studies reporting post-TBI aphasia have concurrently assessed for prosodic processing, despite prosodic processing deficits being common among aphasic patients [6567]. This is especially important for patients who experience communication difficulties post-TBI despite scoring above cut-offs for typical standardized language tests, as the real issue may be prosodic processing impairments that are scarcely assessed in these tests.…”
Section: Discussionmentioning
confidence: 99%
“…One early study compared the performance of PWA and age-and hearingmatched controls on a task requiring attention to speech in the presence of steady-state noise maskers, that is, a condition presumably involving high EM but relatively little IM, and found that PWA performance was poorer than that of controls (Winchester & Hartman, 1955). A more recent study examined the ability of PWA to identify and selectively attend to target speech while ignoring different types of competing auditory information, including both speech maskers and noise maskers (Rankin et al, 2014). The results from this second study indicated that PWA demonstrated a poorer ability to receptively process speech under masked conditions than did controls of similar age and hearing status and that this difference was present when either speech or noise maskers were used.…”
Section: Motivation For Investigating Em and Im In Aphasiamentioning
confidence: 99%
“…(2017) for a series of recent reviews], has high relevance for everyday communication, as real-world conversations often take place in settings that are acoustically complex. While the majority of past research on receptive speech processing in persons with aphasia (PWA) has focused on auditory language comprehension in quiet settings, several recent studies have directly investigated the ability of persons with aphasia (PWA) to selectively attend to and understand speech in the presence of auditory maskers [e.g., Rankin et al (2014) and Villard and Kidd (2019) ]. These studies have provided evidence that PWA—even, in some cases, PWA with milder aphasia types thought to be characterized primarily by expressive language deficits—require higher target-to-masker ratios (TMRs) than do age-matched controls in order to successfully understand target speech.…”
Section: Introductionmentioning
confidence: 99%